THE IMPLEMENTATION OF SISTER PROVINCE COOPERATION : A CASE STUDY OF YOGYAKARTA - Nurseta, Catur Cahya (FIA UB, 2013)
Abstract: The Implementation of Sister Province Cooperation: aCase Study Of Yogyakarta. The rapid development of the sister city/province cooperation is becoming increasingly interesting to study, especially to see how far the resultant impact of the cooperation towards resolving various social and economic development problems. Studies about sister province cooperation in local government provide as much knowledge to know how local government executes their policy, and how far that implementation supports the local government development. In conducting the implementation, it demands cooperation and participation of all the institutions. Besides, good ability and capability of the implementers also gives contribution to achieve the policy objectives. My study concerns about the implementation of sister province cooperation in Yogyakarta, which covers such implementation aspects as human resources, organizational structure, cooperation procedures, fund allocation, equipment and facilities. This study also explained the supporting and constraining factors in implementation of sister province cooperation in Yogyakarta, which included potencies, leadership, and culture. Key words: sister province cooperation, policy implementation, local government Â Abstrak: Penerapan Kerjasama Sister Province: Studi Kasus Yogyakarta. Pesatnya perkembangan kerjasama antar kota/provinsi diluar negeri menjadi semakin menarik untuk dikaji, khususnya untuk melihat seberapa jauh dampak yang dihasilkan dari kerjasama menuju penyelesaian berbagai masalah pembangunan sosial dan ekonomi. Studi tentang kerjasama antar provinsi di pemerintah daerah memberikan pengetahuan yang banyak tentang bagaimana pemerintah daerah menjalankan kebijakan mereka, dan seberapa jauh pelaksanaannya mendukung pembangunan di daerah. Dalam implementasi kebijakan, menuntut kerjasama dan partisipasi dari semua institusi. Selain itu, kemampuan yang baik dari pelaksana juga memberikan kontribusi untuk mencapai tujuan kebijakan. Studi saya tentang implementasi kerjasama antar provinsi di Yogyakarta meliputi aspek-aspek pelaksanaan seperti sumber daya manusia, struktur organisasi, prosedur kerjasama, alokasi dana, peralatan dan fasilitas. Penelitian ini juga menjelaskan faktor-faktor pendukung dan penghambat dalam pelaksanaan kerjasama provinsi adik di Yogyakarta, yang termasuk potensi, kepemimpinan, dan budaya. Â Kata kunci: kerjasama antar provinsi, implementasi kebijakan, pemerintah daerah